2001
DOI: 10.1111/j.1469-8749.2001.tb00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Infantile spasms: diagnosis and assessment of treatment response by video‐EEG

Abstract: The purpose of this study was to investigate early electroclinical manifestations and evaluate treatment responses by video-EEG in infants with newly diagnosed spasms. Spasms were recorded in 44 infants (27 males, 17 females) before adequate treatment. Mean ages at onset of spasms and at first video-EEG were 5.3 months (range 0.9 to 9 months) and 5.9 months (range 2.4 to 11.5 months) respectively. Thirteen infants had cryptogenic and 31 had symptomatic aetiology. First treatment was vigabatrin in 36 infants. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…However, as with the asymmetric hypsarrhythmic pattern, an asymmetric ictal EEG pattern does correlate with focal or lateralized structural lesions. Asymmetric spasms frequently occur in association with asymmetric ictal patterns (Donat and Lo, 1994;Gaily et al, 1995Gaily et al, , 2001.…”
Section: Ictal Eeg Findingsmentioning
confidence: 99%
“…However, as with the asymmetric hypsarrhythmic pattern, an asymmetric ictal EEG pattern does correlate with focal or lateralized structural lesions. Asymmetric spasms frequently occur in association with asymmetric ictal patterns (Donat and Lo, 1994;Gaily et al, 1995Gaily et al, , 2001.…”
Section: Ictal Eeg Findingsmentioning
confidence: 99%
“…Typical diagnostic criteria for IS include neonatal or infantile myoclonic-type extensions or flexions involving the whole body and characteristically disorganized electroencephalogram (EEG) wave patterns (i.e., hypsarrhythmia) [6]. IS are rare, can be catastrophic in nature, and are associated with a wide variety of neuropathological abnormalities [7].…”
Section: Overviewmentioning
confidence: 99%
“…It should be noted that vigabatrin treatment may make spasms milder. Serial video EEG recordings have shown that during vigabatrin treatment there has been transition of motor spasms to subtle spasms that may remain unnoticed [26]. In contrast, ACTH was effective in 71/119 (59 %) patients [99] and ACTH or prednisolone in 21/30 (70 %) patients [22], for a total of 92/149 (62 %) patients.…”
Section: Tuberous Sclerosis (Ts)mentioning
confidence: 99%